2023
DOI: 10.3390/biomedicines11061683
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of the Antiproliferative Activity of the Novel Chitooligosaccharide–Gallic Acid Conjugate against the SW620 Colon Cancer Cell Line

Abstract: Chitooligosaccharide (COS) and gallic acid (GA) are natural compounds with anti-cancer properties, and their conjugate (COS–GA) has several biological activities. Herein, the anti-cancer activity of COS–GA in SW620 colon cancer cells was investigated. MTT assay was used to evaluate cell viability after treatment with 62.5, 122, and 250 µg/mL of COS, GA, and COS–GA for 24 and 48 h. The number of apoptotic cells was determined using flow cytometry. Proteomic analysis was used to explore the mechanisms of action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…The proteomics study on CHOS-GA-treated SW620 colon cancer cell lines also revealed that the CHOS-GA increased the molecular pathways related to intermediate filament organization and structural constituents of the cytoskeleton, while the CHOS influenced the changes in the ribonucleoprotein complex, cytoplasmic translation, and nucleosome assembly [127]. In this study, keratin 18 was hypothesized to show the anti-cancer effects of the CHOS-GA [127,129]. Additionally, a carboxymethyl CHOS (CM-CHOS) was developed and evaluated for its anti-cancer activity in the H22 tumor-bearing mice model [130].…”
Section: Anti-cancer Activitymentioning
confidence: 94%
See 2 more Smart Citations
“…The proteomics study on CHOS-GA-treated SW620 colon cancer cell lines also revealed that the CHOS-GA increased the molecular pathways related to intermediate filament organization and structural constituents of the cytoskeleton, while the CHOS influenced the changes in the ribonucleoprotein complex, cytoplasmic translation, and nucleosome assembly [127]. In this study, keratin 18 was hypothesized to show the anti-cancer effects of the CHOS-GA [127,129]. Additionally, a carboxymethyl CHOS (CM-CHOS) was developed and evaluated for its anti-cancer activity in the H22 tumor-bearing mice model [130].…”
Section: Anti-cancer Activitymentioning
confidence: 94%
“…CHOS-GA could inhibit gastric cancer cell growth via the induction of the apoptosis pathway with coincidental upregulations of p53, p21, Bax, caspase 9, and caspase 3 proteins [128]. The proteomics study on CHOS-GA-treated SW620 colon cancer cell lines also revealed that the CHOS-GA increased the molecular pathways related to intermediate filament organization and structural constituents of the cytoskeleton, while the CHOS influenced the changes in the ribonucleoprotein complex, cytoplasmic translation, and nucleosome assembly [127]. In this study, keratin 18 was hypothesized to show the anti-cancer effects of the CHOS-GA [127,129].…”
Section: Anti-cancer Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, Saetang et al . (2023) reported a higher anti‐cancer effect of CHOS–gallic acid (CHOS‐GAL) conjugate than CHOS by reducing SW620 cell proliferation. Moreover, CHOS‐GAL conjugate (CGC) inhibited various spoilage and food‐borne pathogen bacteria to a higher extent as compared to CHOS alone.…”
Section: Introductionmentioning
confidence: 99%